Forage–cattle relationships in a communally managed semi-arid savanna in northern Zululand, South Africa - Nyamukanza, C.C; Scogings, P.F; Kunene, N.W (Taylor & Francis, 2021)
Development of extensive livestock production in KwaZulu-Natal is constrained by seasonal variability of rangeland production and low forage nutritional quality. A three-year study was implemented to determine the seasonal variation in herbaceous biomass and chemical composition of veld, animal weight, body condition and blood metabolites in a communal area where farmers wished to commercialise. The period of study was not characterised by unusual climatic conditions. Herbaceous biomass increased in wet months and decreased in dry months. Crude protein concentration was higher in wet seasons than dry seasons. Neutral detergent fibre was generally high. Calves gained 0.53–0.63 kg d–1 during the wet season and took 15 months to reach weaning weight. The mean weights and body condition scores of cows and bulls increased during wet seasons and decreased during dry seasons. Blood urea nitrogen was low in the dry season while creatinine concentrations increased in the dry season and dropped in the wet season. The results indicated that the quantity and quality of forage were insufficient for the development of commercial beef production. Further research is needed to develop and test strategies for improving the availability of nutrients in situations where communal farmers wish to develop livestock production.